PENYEBARAN ISLAM DI TIMUR TENGAH - Sa'dana, Kusuma; Andriani, Risa; Debi Setiawati (Yayasan Literasi Sains Indonesia, 2023)
Islam is a religion that many people know has Arabic origins. Because the first Islam existed or was born after the birth of the Prophet Muhammad SAW. Even though it experienced contradictions from previous teachings, Islam managed to spread outside and was accepted by some Arab nations as well as spread throughout the world until now. Islam also experienced a long history in its spread. Which began in Arabia after the death of the Prophet Muhammad SAW, the Islamic leadership was replaced by friends, namely Khulafur Rasyidin. Up to the small dynasties to the big ones. Also experiencing divisions between nations in the struggle for power. But also experienced a golden age or glory in various fields.